Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/f-08-2019-0092
|View full text |Cite
|
Sign up to set email alerts
|

Identification, classification and shortlisting of performance indicators for hospital facilities management

Abstract: Purpose This paper aims to report on a study that aims to establish a list of systematically classified key performance indicators (KPIs) that are useful for hospital facilities management (FM). Design/methodology/approach A review of literature was conducted to identify indicators that are applicable to hospital FM. Each indicator was classified using a phase–hierarchy (P-H) model, which is a two-dimensional matrix comprising three phases (input, process and output) of facilities services delivery and three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 21 publications
(28 reference statements)
0
16
0
2
Order By: Relevance
“…2.1.2 Performance indicators and POE of hospital facilities management. Performance evaluation is essential for ensuring effective operation of facilities (Lai and Yuen, 2020). According to Woona et al (2014), Vischer emphasizes that the value of a POE is proven to be more important than the data collected itself, indicating that it is more about how the FM department follows up on the findings than it is rather a temperature measure of how the staff are satisfied with the services, and how they are following up to improve the measure.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…2.1.2 Performance indicators and POE of hospital facilities management. Performance evaluation is essential for ensuring effective operation of facilities (Lai and Yuen, 2020). According to Woona et al (2014), Vischer emphasizes that the value of a POE is proven to be more important than the data collected itself, indicating that it is more about how the FM department follows up on the findings than it is rather a temperature measure of how the staff are satisfied with the services, and how they are following up to improve the measure.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the hospital sector, they found that cost and productivity rank highest and satisfaction at third place. Lai and Yuen (2020) and Lai and Man (2018) reviewed the relevance of more than 70 indicators and came up with a short list of 18 hospital performance indicators relevant for FM personell, sorted into the four aspects: physical, safety, environmental and financial. Lai and Yuen (2020) researched how to develop an analytic FM performance evaluation method suitable for hospital buildings.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations